2014
DOI: 10.1177/1096348014525639
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Volunteer Tourism in Thailand: Volunteer Tourists’ Motivations And On-Site Experiences

Abstract: This study examines motivations and on-site experiences of volunteer tourists who participate in volunteer tourism at the Home and Life Orphanage in Phang Nga province, Thailand. An interpretive paradigm using qualitative data collection methods (semi-structured interviews, a focus group, participant observation, and diaries) was adopted. The informants included 24 volunteer tourists. The findings of the study suggest that the volunteer tourists' motivations and on-site experiences are multidimensional. Five m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 43 publications
(120 reference statements)
6
42
1
Order By: Relevance
“…Though several authors have indicated that volunteer tourism in Thailand promotes, or is premised upon, such themes as camaraderie (Broad & Jenkins, 2008), intimacy (Mostafanezhad, 2014), selfconfidence (Proyrungroj, 2014), and sentimentality (Mostafanezhad, 2013a), few have explicitly framed these themes in the context of existential authenticity. Further, the data on which this paper is based indicates that despite the importance of various other motivations-including the acquisition of career skills, the desire to help others, and the need for novelty and adventure-and regardless of such factors as age, duration of participation, level of previous travel experience, and nationality, the most significant and frequently-cited reasons given by volunteers for choosing to participate in community service while visiting Thailand all relate to various dimensions of existential authenticity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though several authors have indicated that volunteer tourism in Thailand promotes, or is premised upon, such themes as camaraderie (Broad & Jenkins, 2008), intimacy (Mostafanezhad, 2014), selfconfidence (Proyrungroj, 2014), and sentimentality (Mostafanezhad, 2013a), few have explicitly framed these themes in the context of existential authenticity. Further, the data on which this paper is based indicates that despite the importance of various other motivations-including the acquisition of career skills, the desire to help others, and the need for novelty and adventure-and regardless of such factors as age, duration of participation, level of previous travel experience, and nationality, the most significant and frequently-cited reasons given by volunteers for choosing to participate in community service while visiting Thailand all relate to various dimensions of existential authenticity.…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies indicate that family bonding is an important motivation for volunteer tourists (Lo & Lee, 2010;Mustonen, 2007;Proyrungroj, 2014), it did not factor heavily in the experiences of the volunteers interviewed in Thailand for this research. This is likely a consequence of the timing of this research, which did not coincide with extended school holiday periods in volunteer-sending countries in Europe and North America.…”
Section: Discovering Others: Volunteer Tourism and Inter-personal Eximentioning
confidence: 94%
See 1 more Smart Citation
“…It is revealed that orphan volunteer tourism generates both positive and negative impacts. The financial benefits to the orphanage and the volunteer tourists as role models for children must be set against the exploitation of children for business purposes and concerns about the emotional and psychological health of young children (Proyrungroj 2014). Tomazos and Butler (2012) in a Mexican case study draw attention to the 'balancing act' of the positive and negative implications of committed volunteers.…”
Section: Volunteer Tourism Research and Debatesmentioning
confidence: 98%
“…Tourism development within orphanages is illustrative of the burgeoning trend of tourism within development projects internationally Butler 2010, 2012;Reas 2013aReas , 2013bReas , 2015Proyrungroj 2014). Tourism development within orphanages is illustrative of the burgeoning trend of tourism within development projects internationally Butler 2010, 2012;Reas 2013aReas , 2013bReas , 2015Proyrungroj 2014).…”
Section: A Case Study Of Development Through Orphanage Tourismmentioning
confidence: 99%